An approach to the Codex aeroscriptus ehrenbergensis through a poscolonial view: Felipe Ehrenberg, identity and the border - Castillo López, Marcela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Felipe Ehrenberg is one of the most important Mexican contemporary artists. His work with Artist´s books in Mexico is relevant because he was a pioneer on the field and promoted its creative facilities and social benefits. The Codex aeroscriptus ehrenbergensis is an Artist´s book created by Ehrenberg which represents a life position and resistance with regards to matters relating to border emerged topics such as migration and Latin American identity.